Preparation method of aluminum-based composite material with high modulus, high strength and high fatigue crack propagation resistance
By introducing in-situ self-generated TiB2 particles into the aluminum alloy material and carrying out specific processing, the problem that existing aluminum alloy materials are difficult to simultaneously improve the elastic modulus, strength and reduce the fatigue crack propagation rate is solved, and the preparation of high-performance aluminum-based composite materials is realized.
Patent Information
- Application Number
- CN202510093183.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-25
AI Technical Summary
Existing aluminum alloy materials are difficult to simultaneously improve elastic modulus, strength and reduce fatigue crack propagation rate, and cannot meet the high performance needs of aviation structural materials.
By proportioning the in-situ self-generated TiB2 particles reinforced aluminum-based composite material with aluminum alloy powder according to different particle sizes, the preparation of ingot billets, plastic forming, solid solution treatment and cold-working plastic deformation treatment were prepared, and an aluminum-based composite material with high elastic modulus, high strength and reduced fatigue crack propagation rate was prepared.
The high elastic modulus, high strength and low fatigue crack propagation rate of aluminum alloy materials are achieved, and the safety and durability of aviation components are improved.
Abstract
Description
Technical Field
[0001] The invention relates to an aluminum-based composite material, in particular to an aluminum-based composite material which simultaneously improves the elastic modulus and strength of aluminum alloy and reduces the fatigue crack growth rate and a preparation method thereof, belonging to the technical field of aluminum alloy materials. Background Art
[0002] Lightweight and high-strength aluminum alloys are widely used in the aviation field. The rapid development of the aviation industry has put forward higher demands on high-performance aluminum alloy materials. Improving the elastic modulus and strength of aluminum alloy materials can further effectively achieve lightweight structures. At the same time, it is necessary to reduce the fatigue crack growth rate to improve the safety and durability of aviation components. Therefore, the development of aluminum-based materials with high modulus, high strength and low fatigue crack growth rate is of great significance to the development of advanced aviation structural materials.
[0003] To improve the strength of aluminum alloy, traditional strategies such as grain boundary strengthening, dispersed phase strengthening, solute atom strengthening and dislocation strengthening are mainly used. However, these methods are difficult to improve the elastic modulus of aluminum alloy, that is, they cannot break through the improvement of the elastic modulus of aluminum alloy materials. At the same time, whether it is grain refinement, increasing dispersed phase or increasing dislocation density, although the strength of aluminum alloy materials can be improved, the strength improvement is also very limited, and these methods inevitably lead to an increase in the fatigue crack growth rate of aluminum alloy materials. The strength and elastic modulus of the material can be improved by material composite, and fine ceramic particles can be formed in situ in aluminum alloy, so that high modulus, high strength and high toughness aluminum-based composite materials can be prepared, which has broad application prospects. However, the introduction of ceramic particles will also refine the grains, increase the dislocation density, reduce the passivation effect of the fatigue crack tip, and reduce the fatigue crack deflection distance, resulting in the fatigue crack growth rate of aluminum-based composite materials being higher than that of the corresponding matrix aluminum alloy.
[0004] In short, the current aluminum alloy alloying method cannot achieve the preparation of aluminum alloy materials with improved elastic modulus, strength and fatigue crack growth resistance. The field urgently needs to design a new organizational structure configuration of aluminum-based composite materials to achieve simultaneous improvement of elastic modulus, strength and fatigue crack growth resistance. Summary of the invention
[0005] In order to overcome the problem that it is difficult to break through the existing technology to improve the elastic modulus, strength and fatigue crack growth resistance of aluminum alloy at the same time, the present invention proposes a high modulus, high strength and high fatigue crack growth resistance aluminum-based composite material and a preparation method, by mixing the in-situ self-generated TiB2 particle reinforced aluminum-based composite material with aluminum alloy powder according to different particle sizes, performing ingot preparation, plastic forming and other processing, and then undergoing solid solution treatment, cold working plastic deformation treatment, and low-temperature aging treatment, to obtain an aluminum-based composite material with high elastic modulus, high strength and reduced fatigue crack growth rate.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing a high modulus, high strength and high fatigue crack growth resistance aluminum-based composite material comprises the following steps:
[0008] (1) preparing aluminum-based composite material powder and aluminum alloy powder: the aluminum-based composite material powder is a TiB2 particle reinforced aluminum-based composite material, the average diameter of the powder is 10-100 microns, and the weight accounts for 20%-90%; the average diameter of the aluminum alloy powder is 50-500 microns; the alloying element composition of the aluminum alloy and the aluminum-based composite material can be the same or different;
[0009] (2) Powder mixing and densification treatment: The two powders with the above-mentioned good ratio are fully mixed and then subjected to densification treatment, and the density of the obtained ingot is ≥99.5%;
[0010] (3) Surface milling and thermoplastic forming: performing surface milling on the above-mentioned ingot to obtain a preform; performing thermoplastic forming on the preform to obtain a dual heterogeneous structure aluminum-based composite material;
[0011] (4) solution treatment and cold working deformation treatment: the dual heterogeneous structure aluminum-based composite material is subjected to solution treatment, wherein the solution treatment includes heating, heat preservation and water quenching steps, and cold working deformation treatment is performed after water quenching, the interval between the start time of the cold working deformation treatment and the end time of the solution treatment is less than or equal to 1 hour, the deformation amount is 2%-30%, and the deformation temperature is -50°C-50°C;
[0012] (5) Aging treatment: subjecting the aluminum-based composite material after the above-mentioned cold working deformation treatment to single-stage aging treatment or double-stage aging treatment.
[0013] Preferably, in the aluminum-based composite material powder, the mass fraction of TiB2 particles is 1-20%, and the average diameter of the TiB2 particles is 50-200 nanometers.
[0014] Preferably, in the step (2), the densification treatment is vacuum degassing and hot isostatic pressing treatment, including: first using a metal sheath, heating temperature is 450-550°C, the internal vacuum degree of the metal sheath is ≥0.1Pa, then hot isostatic pressing, pressure ≥100MPa, hot pressing temperature is 450-550°C, holding time is 2-8h, then continue to keep warm for 12-24h without external pressure, and finally air cool.
[0015] Preferably, in step (3), the thickness or diameter of the prefabricated ingot is 100-600 mm, and the thermoplastic forming is hot rolling or hot extrusion.
[0016] Further preferably, the hot rolling step is: the rolling starting temperature is 450°C, rolling to ~6-10mm, annealing treatment is performed, the annealing temperature is 350°C, and insulation is performed for 0.5h; cold rolling is performed after air cooling, and a ~2-4mm thick aluminum-based composite material thin plate is rolled through multiple passes, and no annealing treatment is performed during the cold rolling process.
[0017] Further preferably, the hot extrusion step is: the extrusion temperature is 420° C., and the thickness is extruded to 2-10 mm.
[0018] Preferably, the solution treatment in step (4) is a single-stage solution treatment or a double-stage solution treatment, wherein the single-stage solution treatment is: 460-490°C, the holding time is 0.5-4h, followed by water quenching, and the transfer time is less than or equal to 15s; the double-stage solution treatment is: 470-500°C for 20-40min and 505°C for 20-40min, followed by rapid water quenching, and the transfer time is less than or equal to 20s.
[0019] Preferably, the cold working deformation treatment in step (4) is rolling or stretching.
[0020] Preferably, the single-stage aging treatment is: temperature 50°C-120°C, and insulation time is 24h-480h.
[0021] Preferably, the two-stage aging treatment is: keeping the temperature at 175°C-195°C for 10-15 minutes, and then keeping the temperature at 65-125°C for 72h-480h.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The present invention provides a high modulus, high strength, high fatigue crack growth resistance aluminum-based composite material and a preparation method thereof, which improves the elastic modulus and strength of the aluminum alloy matrix material while reducing the fatigue crack growth rate through a dual heterogeneous structure of non-uniform ceramic particle distribution and non-uniform grain size distribution. The preparation method and process are simple and easy to operate, and the material preparation, processing, and heat treatment processes involved meet the conditions for industrial production. DETAILED DESCRIPTION
[0024] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0025] Example 1
[0026] A method for preparing a high modulus, high strength and high fatigue crack growth resistance aluminum-based composite material comprises the following steps:
[0027] (1) First, Al-4.0Cu-1.6Mg-0.5Mn (mass fraction, %) aluminum alloy powder and 8wt.% TiB2 particle reinforced Al-4.0Cu-1.6Mg-0.5Mn (mass fraction, %) aluminum-based composite material powder were prepared. The TiB2 particles in the aluminum-based composite material were a mixed salt of NaBF4 and Na2TiF7 in a mass ratio of 2:1. The mixed salt was added into a ceramic crucible and fully reacted in aluminum melt at 850°C for 30 minutes to generate TiB2 particles with an average diameter of 100nm, and the reaction by-products on the surface of the melt were removed; then Al-Cu, Al-Mn master alloy, and pure Mg ingot were added according to the ratio. During the preparation process, mechanical stirring and ultrasonic treatment (stirring speed was 250 rpm, ultrasonic intensity was 2000W / m 2 ) to achieve uniform distribution of TiB2 particles generated in the aluminum melt, obtain 8wt.% TiB2 particle reinforced Al-4.0Cu-1.6Mg-0.5Mn (mass fraction, %) aluminum-based composite material melt, then lead out the composite melt through a ceramic guide tube and use a gas atomization process to break the melt into droplets, and finally form aluminum-based composite material powder after the droplets solidify. Similarly, Al-4.0Cu-1.6Mg-0.5Mn (mass fraction, %) aluminum alloy melt is prepared according to the ratio, and the slag on the surface of the melt is removed and then the aluminum alloy melt is prepared into powder by gas atomization. Among them, the gas atomization process uses argon and nitrogen mixed gas, the aluminum alloy melt powdering process uses a pressure of 9MPa and a gas flow rate of 500m / s; the aluminum-based composite material melt powdering process uses a pressure of 10MPa and a gas flow rate of 600m / s. After screening, the average particle size of the aluminum-based composite material powder is 10 microns, and the average particle size of the aluminum alloy powder is 80 microns.
[0028] (2) The aluminum-based composite material powder is mixed with the aluminum alloy powder in a proportion of 60% by mass and 40% by mass. The two metal powders are fully mixed mechanically, and then vacuum degassed and hot isostatically pressed. A metal sheath is used, the heating temperature is 550°C, and the vacuum degree inside the metal sheath is 0.1Pa. Then, hot isostatic pressing is performed at a pressure of 100MPa, a hot pressing temperature of 550°C, and a holding time of 2h. Then, the heat is maintained for 12h without external pressure, and finally air-cooled. The density of the obtained ingot is ~99.8%.
[0029] (3) The aluminum-based composite material ingot after hot isostatic pressing is surface milled and then hot rolled: the surface of the ingot is milled and the sheath is removed to obtain a preform with a thickness of 600 mm; the preform is hot rolled at a rolling start temperature of 450°C, rolled to a thickness of 6 mm, and annealed at a temperature of 350°C for 0.5 h; cold rolled after air cooling, and an aluminum-based composite material sheet with a thickness of 2 mm is obtained through 15 passes at room temperature, and no annealing is performed during the cold rolling process.
[0030] (4) The thin plate is then subjected to a two-stage solution treatment, wherein the solution treatment process is 500°C for 20 min and 505°C for 40 min, followed by rapid water quenching with a transfer time of less than 10 s; the thin plate is transferred to a rolling mill within 30 min and cold rolled at room temperature with a deformation of 30%.
[0031] (5) Finally, the Al-Cu-Mg sheet was subjected to a double-stage aging treatment with the process parameters of 195°C for 15 minutes and then 125°C for 72 hours to obtain a TiB2 particle reinforced Al-4.0Cu-1.6Mg-0.5Mn aluminum-based composite sheet.
[0032] The room temperature mechanical properties test along the rolling direction shows that the elastic modulus of the TiB2 particle reinforced Al-4.0Cu-1.6Mg-0.5Mn aluminum matrix composite sheet is 78GPa, the yield strength is 500MPa, the tensile strength is 645MPa, and the elongation is 15%; the stress intensity factor range ΔK is 20MPa.m 0.5 The fatigue crack growth rate is 4×10 -4 mm / cycle.
[0033] Example 2
[0034] The method is basically the same as that in Example 1, except that:
[0035] During the preparation of aluminum-based composite materials, the reaction temperature of the mixed salt was 820°C, the reaction time was 45 minutes, the final average diameter of the TiB2 particles was 200nm, and the TiB2 particle content was 20wt.%. The pressure of the aluminum alloy melt powder making process was 8MPa and the gas flow rate was 400m / s; the pressure of the aluminum-based composite melt powder making process was 10MPa and the gas flow rate was 500m / s. The powder was screened to select Al-4.0Cu-1.6Mg-0.5Mn (mass fraction) aluminum alloy powder with an average particle size of 250 microns and TiB2 particles reinforced Al-4.0Cu-1.6Mg-0.5Mn (mass fraction) aluminum-based composite powder with an average particle size of 50 microns. In the aluminum-based composite powder and aluminum alloy powder, the mass fraction of aluminum-based composite powder accounts for 20%. After double-stage solution treatment, cold rolling was carried out at 50°C, and the deformation was 20%.
[0036] The room temperature mechanical properties test along the rolling direction shows that the elastic modulus of the TiB2 particle reinforced Al-4.0Cu-1.6Mg-0.5Mn aluminum matrix composite sheet is 77GPa, the yield strength is 490MPa, the tensile strength is 620MPa, and the elongation is 16%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 3×10 -4mm / cycle.
[0037] Example 3
[0038] The method is basically the same as that of Example 1, except that: the reaction temperature of the mixed salt during the preparation of the aluminum-based composite material is 900°C, the reaction time is 20min, the final TiB2 particle average diameter is 50nm, and the content is 1wt.%. The atomization process uses a mixed gas of argon and nitrogen, the aluminum alloy melt powder process uses a pressure of 8MPa and a gas flow rate of 350m / s; the aluminum-based composite material melt powder process uses a pressure of 9MPa and a gas flow rate of 400m / s. After screening, select Al-4.0Cu-1.6Mg-0.5Mn aluminum-based composite material powder with an average particle size of 100 microns and Al-4.0Cu-1.6Mg-0.5Mn aluminum alloy powder with an average particle size of 500 microns, wherein the mass fraction of TiB2 particles to enhance the aluminum-based composite material is 90%. After solution treatment, cold rolling is performed at -50°C, and the deformation is 10%.
[0039] The room temperature mechanical properties test along the rolling direction shows that the elastic modulus of the TiB2 particle reinforced Al-4.0Cu-1.6Mg-0.5Mn aluminum matrix composite sheet is 74GPa, the yield strength is 450MPa, the tensile strength is 600MPa, and the elongation is 18%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 2.5×10 -4 mm / cycle.
[0040] Example 4
[0041] This embodiment relates to a high modulus, high strength, high fatigue crack growth resistance aluminum-based composite material and a preparation method thereof, comprising the following steps:
[0042] (1) First, powders were prepared in the same manner as in Example 1, except that the alloying element composition, TiB2 particle content and size were different, and the selected powder particle sizes were different. The aluminum alloy powder composition was Al-6.5Zn-2.1Mg-2.0Cu-0.15Zr-0.1Sc (mass fraction, %); the aluminum-based composite material powder was TiB2 particle-reinforced Al-6.5Zn-2.1Mg-2.0Cu-0.15Zr-0.1Sc (mass fraction, %) aluminum-based composite material powder, the mass fraction of TiB2 particles was 6%, and the average diameter of TiB2 particles was 100nm. The aluminum alloy melt powdering process used a pressure of 9MPa and a gas flow rate of 500m / s; the aluminum-based composite material melt powdering process used a pressure of 10MPa and a gas flow rate of 550m / s. After screening, the average particle size of the aluminum alloy powder was 90 microns, and the average particle size of the aluminum-based composite material powder was 30 microns.
[0043] (2) Secondly, the aluminum-based composite material powder is mixed with the aluminum alloy powder with a mass fraction of 70% and the aluminum alloy powder with a mass fraction of 30%. The two metal powders are fully mixed mechanically and then vacuum degassed and hot isostatically pressed. A metal sheath is used, the heating temperature is 450°C, and the vacuum degree inside the metal sheath is 0.5Pa. Then, hot isostatic pressing is performed with a pressure of 150MPa, a hot pressing temperature of 450°C, and a holding time of 8h. Then, the heat is maintained for 24h without external pressure, and finally air-cooled. The density of the obtained ingot is ~99.8%.
[0044] (3) milling the surface of the aluminum-based composite ingot after hot isostatic pressing, the ingot diameter is 300 mm, and then hot extrusion: milling the surface of the aluminum alloy ingot after hot isostatic pressing, removing the jacket, and obtaining a preform; hot extruding the preform at an extrusion temperature of 420° C. to extrude a plate with a cross-section of 10 mm thick and 100 mm wide;
[0045] (4) The plate extruded to a thickness of 10 mm was then subjected to a single-stage solution treatment process, wherein the solution treatment process was to maintain the temperature at 460°C for 4 h, followed by rapid water quenching, with a transfer time of less than 15 s; the plate was transferred to a stretching machine within 1 h and stretched by 2% at room temperature.
[0046] (5) Finally, the plate was subjected to a single-stage aging treatment with the process parameters of 50 °C for 480 h to obtain a TiB2 particle reinforced Al-6.5Zn-2.1Mg-2.0Cu-0.15Zr-0.1Sc aluminum-based composite plate.
[0047] The room temperature mechanical properties test along the extrusion direction shows that the elastic modulus of the TiB2 particle reinforced Al-6.5Zn-2.1Mg-2.0Cu-0.15Zr-0.1Sc aluminum matrix composite sheet is 77GPa, the yield strength is 740MPa, the tensile strength is 790MPa, and the elongation is 14%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 7.2×10 -4 mm / cycle.
[0048] Example 5
[0049] The method is basically the same as that of Example 4, except that: the TiB2 particle reinforced Al-6.5Zn-2.1Mg-2.0Cu-0.15Zr-0.1Sc aluminum-based composite material powder accounts for 40%, and the Al-6.5Zn-2.1Mg-2.0Cu-0.15Zr-0.1Sc aluminum alloy powder accounts for 60%. The ingot has a diameter of 100mm, and is hot extruded into a plate with a thickness of 2mm and a width of 50mm. The solid solution treatment process is 490℃ for 0.5h, followed by rapid water quenching, and the transfer time is less than 15s; it is transferred to a stretching machine within 1h and stretched at room temperature by 3%. Finally, the process parameters for aging treatment of the material are 120℃ for 24h.
[0050] The room temperature mechanical properties test along the extrusion direction shows that the elastic modulus of the TiB2 particle reinforced Al-6.5Zn-2.1Mg-2.0Cu-0.15Zr-0.1Sc aluminum matrix composite sheet is 75GPa, the yield strength is 720MPa, the tensile strength is 760MPa, and the elongation is 15%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 7×10 - 4 mm / cycle.
[0051] Example 6
[0052] The method is basically the same as that of Example 4, except that after powder screening, the average particle size of the TiB2 particle reinforced Al-6.5Zn-2.1Mg-2.0Cu-0.15Zr-0.1Sc aluminum-based composite material powder is 60 microns, and the average particle size of the Al-6.2Zn-2.3Mg-2.3Cu-0.1Zr aluminum alloy powder is 300 microns. The mass fraction of the aluminum-based composite material powder accounts for 90%, and the aluminum alloy powder accounts for 10%.
[0053] The room temperature mechanical property test along the extrusion direction shows that the elastic modulus of the aluminum-based composite material plate of the present invention is 78GPa, the yield strength is 710MPa, the tensile strength is 770MPa, and the elongation is 15%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 6.8×10 -4 mm / cycle.
[0054] Example 7
[0055] (1) First, the method of implementation 1 is used to prepare TiB2 particle reinforced Al-6.5Zn-2.1Mg-2.0Cu-0.15Zr-0.1Sc (mass fraction, %) aluminum-based composite material powder, wherein the mass fraction of TiB2 particles is 8%, and the average diameter of TiB2 particles is 100 nanometers, and Al-4.0Cu-1.6Mg-0.5Mn (mass fraction, %) aluminum alloy powder is prepared. The pressure of the aluminum alloy melt powder making process is 8MPa and the gas flow rate is 450m / s; the pressure of the aluminum-based composite material melt powder making process is 10MPa and the gas flow rate is 550m / s. After screening, aluminum-based composite material powder with an average particle size of 30 microns and aluminum alloy powder with an average particle size of 200 microns are obtained.
[0056] (2) According to the ratio of 60% by mass of aluminum-based composite material powder and 40% by mass of aluminum alloy powder, the two metal powders were fully mixed mechanically, and then vacuum degassing and hot isostatic pressing were carried out. A metal sheath was used, the heating temperature was 480°C, and the vacuum degree inside the metal sheath was 0.1Pa. Then hot isostatic pressing was carried out with a pressure of 100MPa, a hot pressing temperature of 480°C, and a holding time of 4h. Then, the heat preservation was continued for 12h without external pressure, and finally air-cooling was carried out. The density of the obtained ingot was ~99.8%.
[0057] (3) The aluminum-based composite material ingot after hot isostatic pressing is surface milled and then hot rolled: the surface of the ingot is milled and the sheath is removed to obtain a preform with a thickness of 400 mm; the preform is hot rolled at a rolling start temperature of 450°C, rolled to a thickness of 10 mm, and annealed at a temperature of 350°C for 0.5 h; cold rolled after air cooling, and a 4 mm thick aluminum-based composite material sheet is obtained through 15 passes at room temperature, and no annealing is performed during the cold rolling process.
[0058] (4) The thin plate is then subjected to a two-stage solution treatment, wherein the solution treatment process is 470°C for 40 min and 505°C for 20 min, followed by rapid water quenching with a transfer time of less than 10 s; the thin plate is transferred to a rolling mill within 30 min and cold rolled at room temperature with a deformation of 15%.
[0059] (5) Finally, the composite material sheet was subjected to a double-stage aging treatment with the process parameters of 175°C for 10 minutes and then 65°C for 480 hours to obtain an aluminum-based composite material sheet (Al-4.0Cu-1.6Mg-0.5Mn alloy and TiB2 particle reinforcement).
[0060] The room temperature mechanical property test along the rolling direction shows that the elastic modulus of the aluminum-based composite material plate of the present invention is 78GPa, the yield strength is 580MPa, the tensile strength is 690MPa, and the elongation is 15%; the stress intensity factor range ΔK is 20MPa.m0.5 The fatigue crack growth rate is 5.5×10 -4 mm / cycle.
[0061] Comparative Example 1
[0062] The implementation steps of this comparative example are basically the same as those of Example 1, except that: the mass fraction of TiB2 particles with an average particle size of 10 microns reinforced aluminum-based composite material powder (Al-4.0Cu-1.6Mg-0.5Mn) accounts for 10%, the mass fraction of aluminum alloy powder accounts for 90%, and a conventional aging treatment process is adopted. The process parameters are 180°C insulation for 20 hours, and there is no cold deformation treatment before aging.
[0063] The room temperature mechanical properties test along the rolling direction shows that the elastic modulus of the TiB2 particle reinforced Al-4.0Cu-1.6Mg-0.5Mn aluminum matrix composite sheet is 73GPa, the yield strength is 310MPa, the tensile strength is 500MPa, and the elongation is 13%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 6.5×10 -4 Compared with this, the elastic modulus, yield strength and tensile strength of the material in Example 1 of the present invention are all improved, while the fatigue crack growth rate is also significantly reduced.
[0064] Comparative Example 2
[0065] The implementation steps of this comparative example are basically the same as those of Example 2, except that the mass fraction of the 20wt.% TiB2 particle reinforced aluminum-based composite material powder (Al-4.0Cu-1.6Mg-0.5Mn) used is 10%.
[0066] The room temperature mechanical properties test along the rolling direction shows that the elastic modulus of the TiB2 particle reinforced Al-4.0Cu-1.6Mg-0.5Mn aluminum matrix composite sheet is 74GPa, the yield strength is 390MPa, the tensile strength is 520MPa, and the elongation is 12%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 8×10 -4 Compared with this, the elastic modulus, yield strength and tensile strength of the material in Example 2 of the present invention are significantly improved, while the fatigue crack growth rate is reduced by nearly 3 times.
[0067] Comparative Example 3
[0068] The implementation steps of this comparative example are basically the same as those of Example 3, except that the mass fraction of the aluminum-based composite material powder used is 10%, and a conventional aging treatment process is finally adopted with process parameters of 180° C. insulation for 20 hours, and no cold deformation treatment is performed before aging.
[0069] The room temperature mechanical properties test along the rolling direction shows that the elastic modulus of the TiB2 particle reinforced Al-4.0Cu-1.6Mg-0.5Mn aluminum matrix composite sheet is 72GPa, the yield strength is 300MPa, the tensile strength is 480MPa, and the elongation is 15%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 6.2×10 -4 In comparison, the elastic modulus, yield strength and tensile strength of the material in Example 3 of the present invention are all improved, while the fatigue crack growth rate is reduced by more than 2 times.
[0070] Comparative Example 4
[0071] The implementation steps of this comparative example are basically the same as those of Example 1, except that the mass fraction of the aluminum-based composite material powder used is 10%, and the mass fraction of the aluminum alloy powder is 90%.
[0072] The room temperature mechanical properties test along the rolling direction shows that the elastic modulus of the TiB2 particle reinforced Al-4.0Cu-1.6Mg-0.5Mn aluminum matrix composite sheet is 72GPa, the yield strength is 360MPa, the tensile strength is 510MPa, and the elongation is 14%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 5×10 -4 Compared with Example 1, the yield strength and tensile strength of the comparative material are reduced, and the fatigue crack growth rate is large.
[0073] Comparative Example 5
[0074] The implementation steps of this comparative example are basically the same as those of Example 1, except that: aluminum alloy powder with a single particle size distribution and an average particle size of 50 microns is used.
[0075] The room temperature mechanical properties test along the rolling direction shows that the elastic modulus of Al-4.0Cu-1.6Mg-0.5Mn aluminum alloy is 72GPa, the yield strength is 440MPa, the tensile strength is 500MPa, and the elongation is 15%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 5×10 -4Compared with this, the elastic modulus, yield strength and tensile strength of the material in Example 1 of the present invention are all improved while the fatigue crack growth rate is also reduced.
[0076] Comparative Example 6
[0077] The implementation steps of this comparative example are basically the same as those of Example 2, except that: an aluminum alloy powder with a single particle size distribution and an average particle size of 250 μm is used for preparation, and the final aging treatment of the plate adopts conventional aging treatment, and the specific aging process parameters are 180° C. insulation for 20 hours.
[0078] The room temperature mechanical properties test along the rolling direction shows that the elastic modulus of Al-4.0Cu-1.6Mg-0.5Mn aluminum alloy is 72GPa, the yield strength is 330MPa, the tensile strength is 490MPa, and the elongation is 15%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 4.2×10 -4 Compared with this, the elastic modulus, yield strength and tensile strength of the material in Example 2 of the present invention are all improved while the fatigue crack growth rate is also reduced.
[0079] Comparative Example 7
[0080] The specific steps of this comparative example are basically the same as those of Example 2, except that conventional aging treatment is adopted, the specific aging process parameters are 180° C. insulation for 20 h, and no cold working deformation treatment is performed before aging.
[0081] The room temperature mechanical properties test along the rolling direction shows that the elastic modulus of the TiB2 particle reinforced Al-4.0Cu-1.6Mg-0.5Mn composite material is 77GPa, the yield strength is 360MPa, the tensile strength is 520MPa, and the elongation is 12%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 5.5×10 -4 Compared with Example 2, the elastic modulus of the two materials is the same, but the strength of the comparative material is significantly lower and the fatigue crack growth rate is significantly faster.
[0082] Comparative Example 8
[0083] This comparative example involves a preparation and processing method that is basically the same as Example 4, except that: TiB2 particles are used to reinforce aluminum-based composite material powder and conventional aging treatment, the average particle size is 30 microns, the aging treatment process parameters are 120°C insulation for 20 hours, and there is no processing cold deformation treatment before aging.
[0084] The room temperature mechanical properties test along the extrusion direction shows that the elastic modulus of the TiB2 particle reinforced Al-6.5Zn-2.1Mg-2.0Cu-0.15Zr-0.1Sc aluminum matrix composite material is 77GPa, the yield strength is 650MPa, the tensile strength is 700MPa, and the elongation is 8%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 9×10 -4 Compared with Example 4, because the material composition is the same, the elastic modulus of the two are the same, but the tensile strength and elongation of the comparative material are significantly reduced, and the fatigue crack growth rate is increased.
[0085] Comparative Example 9
[0086] This comparative example involves a preparation and processing method that is basically the same as Example 4, except that: aluminum alloy powder with a single particle size distribution is used, and its average particle size is 90 microns.
[0087] The room temperature mechanical properties test along the extrusion direction shows that the elastic modulus of Al-6.2Zn-2.3Mg-2.3Cu-0.1Zr aluminum alloy is 72GPa, the yield strength is 600MPa, the tensile strength is 650MPa, and the elongation is 10%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 8.5×10 -4 Compared with Example 4, the material of this comparative example has a lower elastic modulus, lower strength, and a faster fatigue crack growth rate.
[0088] Comparative Example 10
[0089] This comparative example involves a technical method that is basically the same as that of Example 4, except that conventional aging treatment is adopted, the process parameters are 120°C insulation for 20 hours, and there is no cold working deformation treatment before aging.
[0090] The room temperature mechanical properties test along the extrusion direction shows that the elastic modulus of the TiB2 particle reinforced Al-6.5Zn-2.1Mg-2.0Cu-0.15Zr-0.1Sc composite sheet is 77GPa, the yield strength is 690MPa, the tensile strength is 730MPa, and the elongation is 9%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 9.5×10 -4 Compared with Example 4, the material strength of this comparative example is low and the fatigue crack growth rate is large.
[0091] Comparative Example 11
[0092] This comparative example involves a preparation and processing method that is basically the same as Example 5, except that conventional aging treatment is adopted, the aging process parameters are 120°C insulation for 20 hours, and no cold working deformation treatment is performed before aging.
[0093] The room temperature mechanical properties test along the extrusion direction shows that the elastic modulus of the TiB2 particle reinforced Al-6.5Zn-2.1Mg-2.0Cu-0.15Zr-0.1Sc composite sheet is 75GPa, the yield strength is 640MPa, the tensile strength is 680MPa, and the elongation is 10%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 9×10 -4 Compared with Example 5, the fatigue crack growth rate of the comparative material is high and the strength is reduced.
[0094] Comparative Example 12
[0095] This comparative example involves a technical method that is basically the same as that of Example 6, except that the mass fraction of the aluminum alloy powder used is 90%, and the mass fraction of the aluminum-based composite material powder is 10%.
[0096] The room temperature mechanical properties test along the extrusion direction shows that the elastic modulus of the TiB2 particle reinforced Al-6.5Zn-2.1Mg-2.0Cu-0.15Zr-0.1Sc composite sheet is 73GPa, the yield strength is 620MPa, the tensile strength is 660MPa, and the elongation is 14%; the stress intensity factor range ΔK is 20MPa.m 0.5 When the fatigue crack growth rate is 7.5×10 -4 Compared with Example 6, the material of this comparative example has a lower elastic modulus, lower strength, and a higher fatigue crack growth rate.
[0097] Comparative Example 13
[0098] This comparative example involves a technical method that is basically the same as that of Example 7, except that: the ingot is prepared by using two kinds of powders, both of which are alloys, without adding particles, namely, 40% by mass of Al-4.0Cu-1.6Mg-0.5Mn (mass fraction, %) aluminum alloy powder and 60% by mass of Al-6.5Zn-2.1Mg-2.0Cu-0.15Zr-0.1Sc (mass fraction, %) aluminum alloy powder, and adopting conventional heat treatment process, the solid solution temperature is 500℃, and it is kept for 60min before quenching. After quenching, no cold deformation is carried out, and aging treatment is carried out directly, and it is kept at 180℃ for 20h.
[0099] The room temperature mechanical property test along the rolling direction shows that the elastic modulus of the aluminum alloy plate of the present invention is 72GPa, the yield strength is 410MPa, the tensile strength is 520MPa, and the elongation is 13%; the stress intensity factor range ΔK is 20MPa.m 0.5 The fatigue crack growth rate is 7.0×10 -4 Compared with Example 7, the elastic modulus and strength of the material in this comparative example are significantly lower, and the fatigue crack growth rate is greater.
[0100] The above describes the specific embodiments of the present invention. By comparing the embodiments with the comparative examples, the high modulus, high strength and high fatigue crack growth resistance aluminum-based composite material and the preparation method provided by the method of the present invention can simultaneously improve the strength and fatigue crack growth resistance of aluminum alloy.
[0101] It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various changes or modifications within the scope of the claims, which do not affect the essence of the present invention. In the absence of conflict, the embodiments of the present application and the features in the embodiments may be combined with each other at will.
Claims
1. A method for preparing a high modulus, high strength and high fatigue crack growth resistance aluminum-based composite material, characterized in that: The steps include: (1) preparing aluminum-based composite material powder and aluminum alloy powder: the aluminum-based composite material powder is a TiB2 particle reinforced aluminum-based composite material, the average diameter of the powder is 10-100 microns, and the weight accounts for 20%-90%; the average diameter of the aluminum alloy powder is 50-500 microns; (2) Powder mixing and densification treatment: The two powders with the above-mentioned good ratio are fully mixed and then subjected to densification treatment, and the density of the obtained ingot is ≥99.5%; (3) Surface milling and thermoplastic forming: performing surface milling on the above-mentioned ingot to obtain a preform; performing thermoplastic forming on the preform to obtain a dual heterogeneous structure aluminum-based composite material; (4) solution treatment and cold working deformation treatment: the dual heterogeneous structure aluminum-based composite material is subjected to solution treatment, wherein the solution treatment includes heating, heat preservation and water quenching steps, and cold working deformation treatment is performed after water quenching, the interval between the start time of the cold working deformation treatment and the end time of the solution treatment is less than or equal to 1 hour, the deformation amount is 2%-30%, and the deformation temperature is -50-50°C; (5) Aging treatment: subjecting the aluminum-based composite material after the above-mentioned cold working deformation treatment to single-stage aging treatment or double-stage aging treatment.
2. The method for preparing the high modulus, high strength and high fatigue crack growth resistance aluminum-based composite material according to claim 1, characterized in that: In the aluminum-based composite material powder, the mass fraction of TiB2 particles is 1-20%, and the average diameter of the TiB2 particles is 50-200 nanometers.
3. The method for preparing the high modulus, high strength and high fatigue crack growth resistance aluminum-based composite material according to claim 1, characterized in that: In the step (2), the densification treatment is vacuum degassing and hot isostatic pressing treatment, including: first using a metal sheath, heating temperature is 450-550°C, the internal vacuum degree of the metal sheath is ≥0.1Pa, then hot isostatic pressing, pressure ≥100MPa, hot pressing temperature is 450-550°C, holding time is 2-8h, then continue to keep warm for 12-24h without external pressure, and finally air cool.
4. The method for preparing the high modulus, high strength and high fatigue crack growth resistance aluminum-based composite material according to claim 1, characterized in that: In the step (3), the thickness or diameter of the preform is 100-600 mm.
5. The method for preparing the high modulus, high strength and high fatigue crack growth resistance aluminum-based composite material according to claim 1, characterized in that: In the step (3), the thermoplastic forming is hot rolling or hot extrusion; the hot rolling step is: the rolling starting temperature is 450°C, rolling to 6-10 mm, annealing treatment is performed, the annealing temperature is 350°C, and the temperature is kept for 0.5h; cold rolling is performed after air cooling, and a 2-4 mm thick aluminum-based composite material thin plate is rolled through multiple passes, and no annealing treatment is performed during the cold rolling process; the hot extrusion step is: the extrusion temperature is 420°C, and the plate is extruded to 2-10 mm thick.
6. The method for preparing the high modulus, high strength and high fatigue crack growth resistance aluminum-based composite material according to claim 1, characterized in that: The solution treatment in step (4) is a single-stage solution treatment or a double-stage solution treatment, wherein the single-stage solution treatment is: 460-490°C, the holding time is 0.5-4h, followed by water quenching, and the transfer time is less than or equal to 15s; the double-stage solution treatment is: 470-500°C for 20-40min and 505°C for 20-40min, followed by rapid water quenching, and the transfer time is less than or equal to 20s.
7. The method for preparing the high modulus, high strength and high fatigue crack growth resistance aluminum-based composite material according to claim 1, characterized in that: The cold working deformation treatment in step (4) is rolling or stretching.
8. The method for preparing the high modulus, high strength and high fatigue crack growth resistance aluminum-based composite material according to claim 1, characterized in that: The single-stage aging treatment is as follows: the temperature is 50-120°C and the insulation time is 24h-480h; the double-stage aging treatment is as follows: the temperature is 175°C-195°C for 5-15min, and then the temperature is 65-125°C for 72h-480h.
Citation Information
Patent Citations
Nano AlN particle reinforced mixed crystal heat-resistant aluminum-based composite material and preparation method
CN110592412A
Composite material with in-situ synthesized particles and preparation method of composite material
CN112176212A
High-modulus, high-strength and high-toughness aluminum-based composite material and preparation method thereof
CN113755726A
Aluminum alloy profile with fatigue crack propagation resistance and preparation method of aluminum alloy profile
CN117418178A
Heterogeneous layered structure aluminum-based composite material and preparation method thereof
CN118006960A